1998
DOI: 10.1037/1061-4087.50.2.78
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of hardiness training.

Abstract: Recent research has suggested that hardiness protects wellness and stimulates effective functioning despite stressful circumstances. This study continued evaluation of the effectiveness of a hardiness training program. With managers as participants, the hardiness training condition was compared with a relaxation/meditation condition and a placebo/social support control. The hardiness training condition was more effective than the other 2 conditions in increasing self-reported hardiness, job satisfaction, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
102
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(114 citation statements)
references
References 32 publications
6
102
0
6
Order By: Relevance
“…For example, Stemarie, Gupta, & Derevensky, [8] found that adolescent gamblers report more anxiety and social stress compared to nongamblers. Further, Hayatbakhsh, Clavarino, Williams, Bor, and Najman [9] found that adolescents who smoke, externalize problems, perform poorly in high school, or experienced childhood sexual abuse are more likely to be gambling when they are 21 years of age. Also, Lalande, Bastille-Denis, Savard, Jacques, Leclerc, & Giroux [10] report that by comparison with gamblers, those who do not gamble show optimism, expectation of success, and well-being.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Stemarie, Gupta, & Derevensky, [8] found that adolescent gamblers report more anxiety and social stress compared to nongamblers. Further, Hayatbakhsh, Clavarino, Williams, Bor, and Najman [9] found that adolescents who smoke, externalize problems, perform poorly in high school, or experienced childhood sexual abuse are more likely to be gambling when they are 21 years of age. Also, Lalande, Bastille-Denis, Savard, Jacques, Leclerc, & Giroux [10] report that by comparison with gamblers, those who do not gamble show optimism, expectation of success, and well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Maddi (2004Maddi ( , 2006 considers hardiness more in terms of a cognitive/emotional amalgam consisting of three related attitudes (i.e., commitment, control and challenge) that is learned early in life but that can still be enhanced in adulthood through training interventions. Across several studies Maddi and associates have been able to demonstrate the effectiveness of hardiness training in both students and working adults (e.g., Maddi, 1987;Maddi, Harvey, Khoshaba, Fazel, & Resurreccion, 2009;Maddi, Kahn, & Maddi, 1998). Below we provide a short overview of the existing literature and research on hardiness development.…”
mentioning
confidence: 99%
“…Psychological hardiness, originally derived from existential psychology, is a personality trait that is a promising resource for maintaining wellness (Maddi & Hightower, 1999;Maddi, Kahn, & Maddi, 1998). Hardiness is defined as a source of resistance against the negative effects from stressful life events (Kobasa & Puccetti, 1983).…”
Section: Personal Qualitiesmentioning
confidence: 99%
“…Hardy individuals tend to use transformational coping processes that reduce the likelihood of wellness breakdown. The appraised stress attached to life events are decreased through deepened understanding of the circumstances, a broadened perspective, positive reinterpretation, and decisive action (Maddi & Hightower, 1999;Maddi, Kahn, & Maddi, 1998).…”
Section: What Specific Challenges Do Youth Face In Being Street Involmentioning
confidence: 99%
See 1 more Smart Citation